A Study of Language Learning Strategies for Practical Use through the Process of Cooperative Learning - Likitrattanaporn, Wannakarn (International Journal of Educational Technology and Learning, 2018)
The purposes of this investigation were 1) to find out the average students’ use of language learning strategies 2) to examine the students’ opinions towards cooperative learning and 3) to investigate the efficiency of the cooperative learning reflecting on the students’ practical use of language learning strategies. Research hypothesis of this study is whether the students can gain and apply the knowledge of how to use language learning strategies through their interaction, exchanging information or ideas, brainstorming in cooperative learning activity or not. The participants were 79 Thai undergraduate students minoring in Linguistic Program at Srinakharinwirot University, Bangkok, Thailand. The research instruments were 1) Strategy Inventory for Language Learning (SILL) Version 7.0 by Rebecca L. Oxford adapted by Park Bun-seon, Kwon Mi-jeong and Hwang Jung-hwa in 1998 and 2) a questionnaire designed to ask the students' opinions towards cooperative learning. It was found out that 49% of the students sometimes used language learning strategies, 47% of them usually used language learning strategies and 4 % of them generally not used language learning strategies. It was discovered that the students showed positive opinions towards cooperative learning. Exchanging information through cooperative learning assists them to gain more language learning strategies from peers that can be applied to use in learning L2 later.